Sekolah Sahabat Gawai: Pendampingan Kegiatan Belajar dari Rumah untuk Menjaga Kesehatan Siswa SMP Islam Dian Didaktika - Nurfitri Bustamam; Duma Lumban Tobing; Evin Novianti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2021)
In the Academic Year 2020/2021 learning face-to-face for school students in most parts of Indonesia is prohibited to prevent the spread of coronavirus disease (COVID)-19. Instead, a school from home (SFH) is implemented. As a result, the use of gadgets by school students increases not only for learning activities, but also for communication, entertainment/recreation, and socializing. Excessive use of the gadget will increase the risk of developing health problems both physically and mentally. Based on this, the school collaborated with a team from the Faculty of Medicine and the Faculty of Health Sciences Universitas Pembangunan Nasional Veteran Jakarta to carry out community service activities with the theme